Analogue of the Mahler — Sprindžuk’s theorem for polynomials of the second degree in two variables - Sliesoraitienė, R. (Lithuanian Mathematical Journal, 1969)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Р. Слесорайтене. Аналог теоремы Малера—Спринджука для полиномов второй степени от двух переменныхR. Sliesoraitienė. Malerio — Sprindžiuko teoremos analogas antros eilės dviejų kintamųjų polinomams